2014
DOI: 10.7314/apjcp.2014.15.16.6969
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Assessment of Leukemia in Kazakhstan, 2003-2012

Abstract: Cancer is a major health problem facing the entire world, and Kazakhstan is not the exception. The aim of this study was to present an epidemiological assessment of leukemia in the population of Kazakhstan during 2003-2012. This descriptive and retrospective study was based on data obtained from all oncological organizations of the whole country. Age standardized incidence rates per 100,000 population for leukemia were calculated. Totally, 6,741 new cases of leukemia were registered in Kazakhstan during the 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…Mortality was the highest in an older age group (>70 years) in both men and women. This result is consistent with that of a study in the United States that reported a leukemia-related mortality rate of 2.9/100 000 versus 60/100 000 in men aged <65 versus ≥65 years, respectively, and 2.0/100 000 versus 32/100 000 in women aged <65 versus ≥65 years, respectively ( Igissinov et al, 2014 ). Compared with the mortality rate, which is usually higher in the elderly, the AYLL lends greater weight to age for diseases that result in younger deaths and less weight to age for diseases affecting the elderly ( Pham, Fujino, Matsuda, & Yoshimura, 2010 ).…”
Section: Discussionsupporting
confidence: 92%
“…Mortality was the highest in an older age group (>70 years) in both men and women. This result is consistent with that of a study in the United States that reported a leukemia-related mortality rate of 2.9/100 000 versus 60/100 000 in men aged <65 versus ≥65 years, respectively, and 2.0/100 000 versus 32/100 000 in women aged <65 versus ≥65 years, respectively ( Igissinov et al, 2014 ). Compared with the mortality rate, which is usually higher in the elderly, the AYLL lends greater weight to age for diseases that result in younger deaths and less weight to age for diseases affecting the elderly ( Pham, Fujino, Matsuda, & Yoshimura, 2010 ).…”
Section: Discussionsupporting
confidence: 92%
“…Similar studies in USA concerning blood cancer in Europe and USA in 2005 showed that overall incidences for hematopoietic malignancies have been raised along western countries and AML incidence had slow decrease or stable trend in the most European countries but it has been surged in Wales and England about 70% from 1971 for both sexes (Rodriguez-Abreu et al, 2007). Also researches have shown that different blood cancer incidence are higher among men (than women) which is comparable in the countries including Iran, Kazakhstan, Croatia, European union and United states (Coebergh et al, 2006;Tahmasebi et al, 2006;Rodriguez-Abreu et al, 2007;Hejazi et al, 2010;Sant et al, 2010;Dastgiri et al, 2011;Farahmand et al, 2011;Modak et al, 2011;Smith et al, 2011;Dores et al, 2012;Novak et al, 2012;Rajabli et al, 2013) and higher incidence among men may be attributed to genetically or environmental factors (Rajabli et al, 2013;Igissinov et al, 2014).…”
Section: Discussionmentioning
confidence: 91%
“…During a study which was done by Tahmasebi et al in Mazandaran province during 1996-2003, an increasing trend for 8 years period was observed, with non-Hutchkin lymphoma as the highest incidence rate and myeloma leukemia has the lowest incidence rate (Tahmasebi et al, 2006). Farahmand et al found during their study that standard incidence rate for blood cancer among children during a 8 years' time period i.e.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations